2006
DOI: 10.1111/j.1365-2699.2006.01492.x
|View full text |Cite
|
Sign up to set email alerts
|

Floristic patterns and plant traits of Mediterranean communities in fragmented habitats

Abstract: Unveiling the processes that determine the spatial distribution of species is a central goal for community ecology and biogeography. Hubbell (1997Hubbell ( , 2001 suggested that the dispersal history of biological assemblages, rather than habitat specialization, provides the main explanation for spatial variation. Neutral theory predicts that among-site floristic similarity (beta-diversity or commonality) should decrease logarithmically with increasing geographical distance because ABSTRACT Aim To contrast flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 62 publications
0
19
3
Order By: Relevance
“…As oppose to our hypothesis (H2B) and to studies that found geographical distance a major determinant of beta diversity at large-scale (Chust et al, 2006), we found no relation between beta diversity and the average distance between patches at the small scale. Probably at our scale the size and the accessibility of the patches plays more important role than the absolute distance between patches.…”
Section: Beta Diversitycontrasting
confidence: 86%
“…As oppose to our hypothesis (H2B) and to studies that found geographical distance a major determinant of beta diversity at large-scale (Chust et al, 2006), we found no relation between beta diversity and the average distance between patches at the small scale. Probably at our scale the size and the accessibility of the patches plays more important role than the absolute distance between patches.…”
Section: Beta Diversitycontrasting
confidence: 86%
“…Initially, fragmentation and isolation of habitats might protect their species from being out-competed by species better adapted to increases in temperature and precipitation changes (Kissling et al, 2008). Nonetheless, it can be expected that the fitness of many species will eventually decrease, leading to changes in the composition of the vegetation and to a decrease in local species diversity (Chust et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This is causing a dramatic reduction in biodiversity (Brooks et al 2002;Fahring 2002Fahring , 2003Hoffmeister et al 2005) and strong alteration in plant richness and composition (Bascompte and Rodríguez 2001;Chust et al 2006).…”
Section: Introductionmentioning
confidence: 99%